HLA-DR(+) CD38(+) CD4(+) T Lymphocytes Have Elevated CCR5 Expression and Produce the Majority of R5-Tropic HIV-1 RNA In Vivo - Meditz, Amie L. (American Society for Microbiology, 2011)

(untitled)
Percentages of activated T cells correlate with HIV-1 disease progression, but the underlying mechanisms are not fully understood. We hypothesized that HLA-DR(+) CD38(+) (DR(+) 38(+)) CD4(+) T cells produce the majority of HIV-1 due to elevated expression of CCR5 and CXCR4. In phytohemagglutinin (PHA)-stimulated CD8-depleted peripheral blood mononuclear cells (PBMC) infected with HIV-1 green fluorescent protein (GFP) reporter viruses, DR(−) 38(+) T cells constituted the majority of CCR5 (R5)-tropic (median, 62%) and CXCR4 (X4)-tropic HIV-1-producing cells (median, 61%), although cell surface CCR5 and CXCR4 were not elevated in this subset of cells. In lymph nodes from untreated individuals infected with R5-tropic HIV-1, percentages of CCR5(+) cells were elevated in DR(+) 38(+) CD4(+) T cells (median, 36.4%) compared to other CD4(+) T-cell subsets (median values of 5.7% for DR(−) 38(−) cells, 19.4% for DR(+) 38(−) cells, and 7.6% for DR(−) 38(+) cells; n = 18; P < 0.001). In sorted CD8(−) lymph node T cells, median HIV-1 RNA copies/10(5) cells was higher for DR(+) 38(+) cells (1.8 × 10(6)) than for DR(−) 38(−) (0.007 × 10(6)), DR(−) 38(+) (0.064 × 10(6)), and DR(+) 38(−) (0.18 × 10(6)) subsets (n = 8; P < 0.001 for all). After adjusting for percentages of subsets, a median of 87% of viral RNA was harbored by DR(+) 38(+) cells. Percentages of CCR5(+) CD4(+) T cells and concentrations of CCR5 molecules among subsets predicted HIV-1 RNA levels among CD8(−) DR/38 subsets (P < 0.001 for both). Median HIV-1 DNA copies/10(5) cells was higher in DR(+) 38(+) cells (5,360) than in the DR(−) 38(−) (906), DR(−) 38(+) (814), and DR(+) 38(−) (1,984) subsets (n = 7; P ≤ 0.031). Thus, DR(+) 38(+) CD4(+) T cells in lymph nodes have elevated CCR5 expression, are highly susceptible to infection with R5-tropic virus, and produce the majority of R5-tropic HIV-1. PBMC assays failed to recapitulate in vivo findings, suggesting limited utility. Strategies to reduce numbers of DR(+) 38(+) CD4(+) T cells may substantially inhibit HIV-1 replication.